Dental bio-aerosol as a potential occupational hazard: Sources and preventive measures in dental healthcare setting - Ichwan, Solachuddin J. A. (2017)
Dental bio-aerosols are defined as airborne particles of liquid that contain living microorganisms or have been released from living organisms, which are generated during many dental procedures. Dental bio-aerosol has the potential for the airborne spread of disease since air contained within the office is breathed by dental health care workers. Aerosolized microorganism emerges from a patient’s mouth during dental treatment procedures may remain suspended in the air for long periods of time and inhaled into the lungs of a susceptible person. Eliminating the risk of exposure to dental bio-aerosol remains challenging. Dental personnel are urged to make the control of aerosols a standard part of their infection control procedures. To date, various infection control reports and procedures have been published to inform and educate dental health care personnel about the importance of practicing adequate infection control. This brief review highlights the reasons and the potential risks that can be encountered with dental bio-aerosol. Various preventive measures against these risk factors are also discussed.